2024
DOI: 10.1038/s41612-024-00586-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the Madden-Julian oscillation on spring and autumn afternoon diurnal convection in Sri Lanka

Wan‑Ru Huang,
Suranjith Bandara Koralegedara,
Tzu-Yang Chiang
et al.

Abstract: This study examines the impact of strong Madden-Julian Oscillation (MJO) phases (P1–P8) on diurnal rainfall patterns focusing on Afternoon Diurnal Convection (ADC) events in Sri Lanka during 2001–2020 spring and autumn. Daily mean rainfall increases (decreases) during the P2-to-P3 (P6-to-P7) MJO phases in both seasons, while the diurnal rainfall amplitude peaks during the P2-to-P3 (P8-to-P1) MJO phases in spring (autumn). ADC events also occur more frequently and intensely during MJO P2-to-P3 (P8-to-P1) in spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…Given the importance of canonical IOD seasonality (e.g., Zhang et al 2020), we have examined the effect of IOD on the Sri Lanka rainfall during the IOD peak season rather than the rainy season timescale. Recent studies suggest that due to the global warming, severe drought and flood conditions would be expected (Roudier et al 2016;Ma and Yuan 2024) and, the Madden-Julian Oscillation (MJO) has also been identified as a potential driver of variability in the Indian Ocean climate during autumn (Huang et al 2024). Furthermore, it is noted that there is a strong anomalous rising (sinking) motion over Sri Lanka during the positive (negative) IOD (Jayawardena et al 2024).…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of canonical IOD seasonality (e.g., Zhang et al 2020), we have examined the effect of IOD on the Sri Lanka rainfall during the IOD peak season rather than the rainy season timescale. Recent studies suggest that due to the global warming, severe drought and flood conditions would be expected (Roudier et al 2016;Ma and Yuan 2024) and, the Madden-Julian Oscillation (MJO) has also been identified as a potential driver of variability in the Indian Ocean climate during autumn (Huang et al 2024). Furthermore, it is noted that there is a strong anomalous rising (sinking) motion over Sri Lanka during the positive (negative) IOD (Jayawardena et al 2024).…”
Section: Discussionmentioning
confidence: 99%